ZASADY TECHNIKI PRAWODAWCZEJ W PRAKTYCE WYKŁADNI PRAWA - Piszko, Robert (Wydział Prawa i Administracji UAM, 2002)
The conviction about the existence o f certain correspondence between the directives o f editing and interpreting legal texts is based upon the belief that it is the legislator that sets out the linguistic and axiological limits of law application of a legal text; this conviction is also connected with the developed notion o f rational legislator. However, initially one did not use to speak o f the need to create correspondence between the directives of editing and interpreting legal texts in spite of the fact that one was aware of the connection between law creation and interpretation. The author sets out to determine: (i) which of the previously foreseen ways of attaining correspondence was applied during the creation of the official set of legislative technique principles, (ii) whether and to what extent correspondence between legislative technique principles and literal law interpretation directives was attained, and (iii) to what extent the „Legislative Technique Principles” o f 1991 has given rise to the conviction of correspondence between the directives o f law creation and interpretation in the legal practice.
LEGISLATIVE TECHNIQUE PRINCIPLES IN THE PRACTICE OF LAW INTERPRETATION